IN VITRO PHARMACOLOGICAL SCREENING METHODS FOR ANTI-INFLAMMATORY AGENTS - Us, Jijith; S, Jayakumari (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Context: The development of in vitro methods is important in drug discovery process due to the restriction of animal use in the pharmacological screening process. Objective: The objective of the review was to understand the in vitro pharmacological screening methods for anti-inflammatory agents. Methods: The present review details various in vitro methods available for the screening of activity of therapeutic agents against inflammation. Results: Inhibition and measurement of nitric oxide production, mast cell degranulation, leukocyte adhesion assay, platelet-neutrophil adhesion assay, lipopolysaccharide-induced response assay, N-formyl-methionyl-leucyl-phenylalanine-induced O2 generation by polymorphonuclear cells, and cyclooxygenase assays are discussed in this review. Conclusions: These methods help to understand the real mechanism of inflammation and mediators involved in this process and help to identify new compounds possessing the anti-inflammatory activity.